2002
DOI: 10.1081/dct-120014798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HCFC-123 Exposure to Maternal and Infant Rhesus Monkeys on Hepatic Biochemistry, Lactational Parameters and Postnatal Growth

Abstract: Peroxisome proliferators are a class of nongenotoxic rodent hepatocarcinogens that cause peroxisome proliferation and liver tumors when administered to rats and mice; but other species, including guinea pigs, dogs, and primates are less sensitive or refractory to the induction of peroxisome proliferation. Therefore, rodent peroxisome proliferators are not believed to pose a hepatocarcinogenic hazard to humans. Some peroxisome proliferators produce developmental toxicity in rats that is expressed as suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In mice, TFA as a metabolite of 2-bromo-2-chloro-1,1,1-trifluoro-ethane (halothane) passes the placental barrier and accumulates in the fetus and amniotic fluid [264]. TFA was also found in breast milk of monkeys as metabolite of the refrigerant 1,1,1-Trifluoro-2,2-dichloroethane (HCFC-123) [265], Whereas in two recent studies on rats, TFA did not show any developmental effects with NOAEL of 150 and 382 mg/kg bw per day, respectively [261]. In rabbits, on the other hand, major abnormalities have been observed at 375 and 750 mg/kg bw per day as well as, to a lesser extent, at the lowest dose level of 180 mg/kg bw per day predominantly affecting the eyes [261].…”
Section: Ultra-short-chain Pfas-trifluoroacetic Acidmentioning
confidence: 99%
“…In mice, TFA as a metabolite of 2-bromo-2-chloro-1,1,1-trifluoro-ethane (halothane) passes the placental barrier and accumulates in the fetus and amniotic fluid [264]. TFA was also found in breast milk of monkeys as metabolite of the refrigerant 1,1,1-Trifluoro-2,2-dichloroethane (HCFC-123) [265], Whereas in two recent studies on rats, TFA did not show any developmental effects with NOAEL of 150 and 382 mg/kg bw per day, respectively [261]. In rabbits, on the other hand, major abnormalities have been observed at 375 and 750 mg/kg bw per day as well as, to a lesser extent, at the lowest dose level of 180 mg/kg bw per day predominantly affecting the eyes [261].…”
Section: Ultra-short-chain Pfas-trifluoroacetic Acidmentioning
confidence: 99%
“…In addition to normal evaluations including liver biopsy, the effect of exposure on milk quality (fat and protein content) was evaluated and the levels of HCFC 123 and TFA were determined. While levels of HCFC 123 and TFA were found in the milk and TFA was found in the infants, there was no effect on body weight of the infants (Cappon et al 2002).…”
Section: Acute Toxicitymentioning
confidence: 77%
“…However, another report suggested that the TFA concentrations measured by Duan et al [77] might result from its metabolic generation from longer-chain PFASs, or from elevated local exposure [78]. Both the detection of metabolically generated TFA in mammals and elevated TFA exposure from certain occupational sources have been reported [79][80][81]. If this is the case, concentrations reported by Duan et al [73] might not be representative of the general population.…”
Section: Toxicitymentioning
confidence: 98%